Translocation of Single-Stranded DNA through Single-Walled Carbon Nanotubes - Liu, Haitao (2010)
We report the fabrication of devices in which one single-walled carbon nanotube (SWCNT) spans a barrier between two fluid reservoirs, enabling direct electrical measurement of ion transport through the tube. A fraction of the tubes pass anomalously high ionic currents. Electrophoretic transport of small single stranded DNA oligomers through these tubes is marked by large transient increases in ion current and was confirmed by PCR analysis. Each current pulse contains about 10(7) charges, an enormous amplification of the translocated charge. Carbon nanotubes simplify the construction of nanopores, permit new types of electrical measurements, and may open avenues for control of DNA translocation.